Wort Substrate Consumption and Metabolite Production During Lambic Beer Fermentation and Maturation Explain the Successive Growth of Specific Bacterial and Yeast Species - De Roos, Jonas; Vandamme, Peter; De Vuyst, Luc (Frontiers in Microbiology, 2018)
The present study combined high-throughput culture-dependent plating and culture-independent amplicon sequencing with a metabolite target analysis to systematically dissect the identity, evolution, and role of the microorganisms, substrates, and metabolites during the four-phase fermentation and maturation process of lambic beer production. This led to the following new insights. The changing physicochemical parameters and substrate and metabolite compositions of the fermenting wort and maturing lambic beer provoked several transitions between microbial species and explained the four-step production process. Manual wort acidification with lactic acid shortened the enterobacterial phase and thus kept biogenic amine formation by enterobacteria present during the early stages of fermentation at a minimum. Growth advantages during the alcoholic fermentation phase caused a transition from the prevalence by Hanseniaspora uvarum and Kazachstania species to that by Saccharomyces cerevisiae and later on Saccharomyces kudriavzevii, due to changing environmental parameters. During the acidification phase, Pediococcus damnosus was prevalent and performed a malolactic fermentation. Acetobacter pasteurianus produced acetic acid and acetoin. Upon maturation, Dekkera species appeared, together with P. damnosus and Pichia membranifaciens, thereby contributing to acetic acid production, depending on the oxygen availability. Moreover, the Dekkera species consumed the acetoin produced by the acetic acid bacteria for redox balancing. The breakdown of maltooligosaccharides seemed to be independent of the occurrence of Dekkera species and started already early in the fermentation process.